Older Workers' Adjustments to Plant Closures - Mazerolle, Maurice; Singh, Gangaram (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
This article investigates whether older workers affected by plant closures are more likely to be "discouraged" from participation in the labour force and to be "bitter" towards employers as well as whether they are less likely to report "career growth" in subsequent employment situations. The data indicated that older workers are less likely to report the poisoning effect and more likely to report the career-growth effect. In addition, post-closure training activities reduced the likelihood ofthe discour aged-worker effect for the 45-55 âge group. The respondents from the older âge groups who undertook post-closure training activities were more likely to report the poisoning effect and less likely to report the career-growth effect. In the final section, we argue that the results relate to the définition ofthe âge groups, the transferability of human capital, and the value of community support. We also highlight the implications of the results for public and institutional policies.